Oat beta-glucan: Biochemistry, structure and genetic variation. - Miller, S. Shea. (University of Ottawa (Canada), 1992)
An enzymatic assay designed for measurement of $\beta$-glucan in barley was modified to allow measurement of total $\beta$-glucan content in oats by manipulating the grinding and incubation protocol. Using the modified enzymatic assay, the range of genetic and environmental variation of $\beta$-glucan content in Canadian domestic and breeder's lines of oats was assessed using several cultivars grown in 5 locations in eastern Canada in 3 growing seasons. Analysis of variance indicated that the predominant source of variation was genetic. A second assay using Flow Injection Analysis (FIA) to measure $\beta$-glucan was also evaluated. Although a high correlation was observed for the results of the two methods (r = 0.90), the results obtained using FIA tended to be somewhat lower than those obtained using the modified enzymatic assay: the enzymatic assay was judged to be more accurate for estimation of total $\beta$-glucan in oats. Nevertheless, because of its greater speed and simplicity, FIA would be a valuable screening tool for routine-applications. Using the enzymatic assay, $\beta$-glucan content was also measured in 18 primitive species of Avena to evaluate possible sources of germplasm for expanding the range of $\beta$-glucan content currently available in domestic cultivars. A comparison of $\beta$-glucan content with protein content, oil content and thousand kernel weight in domestic oats showed that these quality parameters are independent of $\beta$-glucan concentration in oats. Scanning microspectrofluorometry was used to map $\beta$-glucan distribution in single kernels of oats: differences were observed within single kernels, and also among kernels from different cultivars of oats. Microscopic examination suggests that the different distribution patterns are due to differences in cell wall thickness adjacent to the germ and around the periphery of the kernel, and also to differences in cell size and shape in the central endosperm. A high $\beta$-glucan (Marion) and a low $\beta$-glucan oat cultivar (OA516-2) were selected for isolation and preliminary characterization of the endosperm cell walls, which are the major source of $\beta$-glucan in the oat kernel. It was concluded that the differences in $\beta$-glucan content that were observed in whole groats were not due to differences in the composition of isolated endosperm cell walls, but to variation in cell size and cell wall thickness in different areas of the groats. (Abstract shortened by UMI.)
Keywords: Chemistry, Biochemistry.